Adult Acne in Middle-age: Effects on Mental Health in General Population of the Northern Finland Birth Cohort 1966 - Marjukka Leskelä; Jari Jokelainen; Laura Huilaja; Suvi-Päivikki Sinikumpu (Medical Journals Sweden, 2024)
The impact of adult acne on patients' mental health has not been widely studied, and most studies have been conducted within specific patient populations. The current study examines the association between adult acne and psychological symptoms in the Northern Finland Birth Cohort 1966 (NFBC1966) (n = 1,907). The cohort members attended a health study at the age of 46 years, which comprised a whole-body examination performed by dermatologists to identify acne, and answering the Beck Depression Inventory II (BDI-II), Athens Insomnia Scale (AIS), Generalized Anxiety Disorder (GAD-7), State-Trait Anxiety Inventory (STAI) and 15-dimensional measure of health-related quality of life (15D HRQoL) questionnaires. The prevalence of adult acne was 7.9% (n = 150) with no statistical differences between the sexes. Cases with acne presented more (18.9%) depressive symptoms (BDI-II > 14 points) compared with those without acne (9.7%) (p < 0.001). In adjusted logistic regression analyses, those with acne had a 2-fold risk (odds ratio (OR) 2.08, 95% confidence interval (95% CI) 1.23-3.38) of having depressive symptoms compared with controls. In conclusion, when treating adult acne patients, it is important to recognize the increased risk of mental health symptoms.